1974
DOI: 10.5006/0010-9312-30.2.47
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of Hydrogen on Pitting Corrosion and Stress Corrosion of Austenitic Stainless Steel in Chloride Environment

Abstract: In a study on the mechanism of pitting corrosion, a gas evolution in the pit has been observed. This gas has been gaschromatographically identified as hydrogen. The explanation of the evolution of hydrogen by the acidification of the pit electrolyte and the potential drop across the pit have been experimentally proved. By means of vacuum extraction experiments, the diffusion and dissolution of hydrogen in the metal has been shown. Experiments have been carried out to determine the effects of the dissolved hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
4

Year Published

1977
1977
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 0 publications
1
15
0
4
Order By: Relevance
“…18 The Urbach tail can be characterized by the following relationship 19,20 [3] where h is the photon energy, E opt ϭ optical gap, k ϭ Boltzmann's constant (8.620 ϫ 10 Ϫ5 eV/K) and T ϭ temperature in kelvin. ␣ 0 and ␥ are constants.…”
Section: Resultsmentioning
confidence: 99%
“…18 The Urbach tail can be characterized by the following relationship 19,20 [3] where h is the photon energy, E opt ϭ optical gap, k ϭ Boltzmann's constant (8.620 ϫ 10 Ϫ5 eV/K) and T ϭ temperature in kelvin. ␣ 0 and ␥ are constants.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that hydrogen increases the corrosion rates of precharged austenitic stainless steels (SS) and carbon steels. [3][4][5] For austenitic SS, hydrogen has been reported to promoted anodic dissolution, to decrease the stability of the passive film, 6 and to increase pitting susceptibility. 7 Both hydrogen and stress have been found to facilitate anodic dissolution in a synergistic manner.…”
Section: Introductionmentioning
confidence: 99%
“…Prisustvo hloridnih jona onemogućava repasivaciju površine na dnu pita, koja se ubrzano anodno rastvara. Tokom hidrolize metalnih jona na dnu pita dolazi do smanjenja pH vrednosti rastvora [5]. Pokazano je da je kod nerđajućih čelika u neutralnim hloridnim rastvorima (0.5 mol dm -3 NaCl) pH vrednost rastvora unutar pita niža od 1, dok je koncentracija hloridnih jona 6,2 mol dm -3 [6].…”
Section: Uvodunclassified
“…; [1], [2,3], [4][5][6][7][8], Skraćene naziva časopisa treba navoditi prema Međunarodnom kodeksu za skraćivanje naslova periodičnih publikacija (http://www.efm.leeds.ac.uk/~mark/ISIabbr/).…”
Section: Uvodunclassified